What Really Drives Value Co-Creation? Rethinking Relationship Quality in GoFood’s Sharing Economy Platform - Yahya Abdurrahman Adib; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2026)
This research examines how relationship quality influences consumer value co-creation within food delivery sharing economy platforms, with a specific focus on GoFood users from Generation Z at Universitas Negeri Jakarta. It aims to determine the effects of trust, commitment, and satisfaction shape students’ intentions to participate in value co-creation activities. Employing a quantitative survey approach, data from 52 GoFood consumers, which were analyzed through PLS-SEM. Results indicate that commitment has a positive and significant effect on value co-creation intentions, while trust and satisfaction do not show significant direct effects. These results suggest that relational attachment plays a more critical role than evaluative perceptions in motivating co-creation behavior among Generation Z users. The research adds to the literature by highlighting the differentiated roles of relationship quality dimensions in sharing economy platforms and by providing context-specific insights into food delivery services. Practically, the findings imply that platform providers should prioritize strategies that strengthen user commitment to encourage active participation and value co-creation.